Psychology and Personality Types of Infertile and Fertile Women - hamad, Abdulqader; ali, Sirwan (Iraqi National Journal of Nursing Specialties, 2013)
Objective(s): To determine the prevalence and predisposing factors of psychology & personality types amonginfertile and fertile women attending in Complex Imam Khomeini Hospital.Methodology: A total of 150 infertile women from Vali-Asr Reproduction Health Research Center and 150 fertilewomen from the Gynecology Clinic of Imam Khomeini Hospital in Tehran / Iran were chosen by simplerandomization. Data was obtained by using Eysenck personality (EPQ) and structured researcher questionnaires.Results: showed that based on Eysenck personality questionnaire (EPQ), personality instability was more commonamong infertile women than fertile women; this relationship was statistically significant (P